(untitled) (Medical Forum Monthly, 2024)
Objective: To provide the spectrum of ocular trauma, their potential hazards and propose preventive measures. Study Design: Retrospective Descriptive Place and Duration of Study: This study was conducted in the departments of Anwar Paracha Eye Hospital (APEH) & Forensic Medicine Ghulam Mohammmad Mahar Medical College Sukkur (GMMMCS) & Chandka Medical College Larkana (CMCL), constituent colleges of Shaheed Mohtarma Benazir Bhutto Medical University Larkana (SMBBMUL) from January to December 2013. Materials and Methods: The present study was conducted from the records of patients of ocular injuries who attended Anwar Paracha Eye Hospital GMMMC Sukkur with association of departments of Forensic Medicine of GMMMC Sukkur& CMC Larkana, the constituent colleges of SMBBMUL. Results: Of all patients visited APEH, 1.016% cases were of ocular injuries with Male to Female ratio of 8.34:1. The most vulnerable age group was 11-30 years (67.14%). On presentation in most of cases 130 (46.43%) had visual acuity 6/9 & on follow up 6/6 in 200 (71.43%) cases. The mainly sharp objects in 200 (71.43%) cases were to cause injury and mostly manner of injury was an accident in 212(75.72%) cases. Conclusion: Majority of the cases were male of young age injured by sharp object due to accident with good prognosis of visual acuity